Thin film fluorescence sensor for measuring iron content in catalyst and preparation method thereof
By covering a fluorescent sensor with five layers of fluorescent sensing composite layer film on a quartz-based backsheet, the problem of complex and time-consuming operation of determining the iron content in the catalyst in the prior art is solved, and fast and accurate iron content measurement is achieved, and the fluorescent sensor can Regeneration and reuse.
Patent Information
- Application Number
- CN202010668162.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-07-13
AI Technical Summary
The prior art is complex and time-consuming to determine the iron content in the catalyst, and lacks a simple and fast fluorescence sensor method.
A fluorescent sensor with five layers of fluorescent sensing composite layer films is used to combine magnesium-aluminum hydrotalcite layer plates and wrapped calcein disodium salts to form a fluorescent sensing composite layer film through supramolecular layers. The iron content in the catalyst was determined.
It realizes rapid and accurate determination of iron content in the catalyst, which is easy to operate and quick, and the fluorescent sensor can be regenerated and reused.
Smart Images

Figure BDA0002581216330000041 
Figure BDA0002581216330000042 
Figure HDA0002581216340000011
Abstract
Description
Technical Field
[0001] The present invention relates to a fluorescence sensor and a preparation method thereof, in particular to a thin film fluorescence sensor for measuring metal ions in a sample and a preparation method thereof. Background Art
[0002] The catalytic reforming process uses naphtha as raw material to produce high-octane gasoline and BTX (benzene, toluene, xylene) aromatics, and produces hydrogen as a by-product. It is one of the main processing technologies in modern oil refining and petrochemical industries. For reforming catalysts, the walls of the equipment and metal parts on the device are constantly in contact with water, air and corrosive HCL, which causes corrosion. The generated rust comes into contact with the catalyst, causing the iron content of the reforming catalyst to increase continuously. In addition, iron is inevitably introduced into the catalyst during the process of starting up the device and loading the agent and during the reaction process. Iron is a common metal poison in reforming catalysts. It can strongly combine with metal platinum to form a stable compound, causing irreversible poisoning. Therefore, it is extremely important to detect the iron content in the reforming catalyst.
[0003] The common methods for determining the iron content in reforming catalysts include colorimetry, atomic absorption spectrometry, and inductively coupled plasma atomic emission spectrometry (ICP / AES). Although these methods have high sensitivity, the experimental operating conditions are relatively complex and time-consuming. Therefore, it is particularly important to develop a simple and fast fluorescent sensor for the detection of iron content in reforming catalysts.
[0004] Fluorescence sensors have attracted much attention due to their high sensitivity, rich signal collection, and ease of use, and have developed rapidly in recent years. Fluorescence sensors are mainly divided into two categories: one is a homogeneous fluorescence sensor used in solution, and the other is a thin film fluorescence sensor. Thin film fluorescence sensors have unique advantages such as repeatability, maintaining the components of the system to be tested, no reagent consumption, and easy deviceization. The research on thin film fluorescence sensors has become one of the most active branches in monolayer chemistry research today and has become a research hotspot in recent years.
[0005] Layered double hydroxides (LDHs) are hydrotalcite-type layered compounds, which are new multifunctional layered materials with good chemical stability. The main layer skeleton has positive charges, the anions between the layers have corresponding negative charges, and the substances in the interlayer channels are exchangeable. Therefore, they can be used to prepare fluorescent sensors. CN102053079A discloses a magnesium ion fluorescent sensor and a preparation method, which uses zinc-aluminum hydrotalcite and inserts 1-naphthylamine-3.6.8-trisulfonic acid between its layers as a fluorescent material for determining the magnesium ion content in a solution.
[0006] CN105866087A discloses a melamine concentration fluorescent sensor and a preparation method, which uses a zinc-aluminum hydrotalcite or a magnesium-aluminum hydrotalcite precursor, inserts a chromotropic acid sodium salt into the hydrotalcite precursor by forming a nano-silver cluster solution of a chromotropic acid sodium salt, and performs layer-by-layer self-assembly to prepare a fluorescent sensor. The fluorescent sensor has good selectivity for melamine and is linear within a certain range. Summary of the invention
[0007] The object of the present invention is to provide a thin film fluorescence sensor for determining the iron content in a catalyst and a preparation method thereof. The thin film fluorescence sensor is used for rapidly determining the iron content in a catalyst, has good accuracy, is convenient and quick to operate, and can be regenerated and reused.
[0008] The thin film fluorescence sensor for measuring the iron content in a catalyst provided by the present invention comprises a quartz substrate and five layers of fluorescence sensing composite layer films covered thereon, wherein the quartz substrate comprises a quartz sheet and an assembly-aiding layer loaded on the quartz sheet, wherein the assembly-aiding layer is a diethylene glycol phthalate diacrylate layer, and the upper layer of each layer of the fluorescence sensing composite layer film is a magnesium aluminum hydrotalcite layer, and the lower layer is a polystyrene sulfonate layer containing disodium calcein.
[0009] The present invention encapsulates the fluorescent indicator calcein disodium salt in sodium polystyrene sulfonate, combines it with magnesium aluminum hydrotalcite layer plates, and uses a supramolecular layer-by-layer self-assembly method to form a fluorescent sensing composite layer film to prepare a fluorescent sensor. The fluorescent sensor can be used to determine the iron content in the reforming catalyst, and the operation is convenient and quick. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 X-ray diffraction (XRD) patterns of magnesium aluminum carbonate hydrotalcite (MgAl-CO3-LDH) and magnesium aluminum nitrate hydrotalcite (MgAl-NO3-LDH) synthesized in Example 1 of the present invention.
[0011] Figure 2 This is a scanning electron microscope (SEM) image of the magnesium aluminum hydrotalcite synthesized in Example 1 of the present invention, wherein A is MgAlCO3-LDH and B is MgAlNO3-LDH.
[0012] Figure 3 The fluorescence intensity values of the fluorescence sensor having five fluorescence sensing composite layer films prepared by using mixed solutions of sodium polystyrene sulfonate and disodium calcein salt of different concentrations in various examples of the present invention.
[0013] Figure 4 This is the UV-visible absorption spectrum of the fluorescent sensor with different numbers of fluorescent sensing composite layers prepared in Example 2 of the present invention.
[0014] Figure 5The fluorescence intensity values of the fluorescence sensing composite layer films with different numbers of layers in the fluorescence sensor prepared in Example 2.
[0015] Figure 6 The fluorescence intensity values of FeCl3 solutions with different iron ion contents were measured using the fluorescence sensor prepared in Example 2 of the present invention.
[0016] Figure 7 The fluorescence intensity values of the fluorescence sensor prepared for the present invention before and after use and after regeneration. DETAILED DESCRIPTION
[0017] The present invention utilizes the characteristics that the main layer of magnesium-aluminum hydrotalcite carries positive charge and the guest molecule carries negative charge, adopts the layer-by-layer self-assembly method, and forms the guest molecule calcein disodium salt (also called calcein sodium salt, C 30 H 24 N2Na2O 13 ) is wrapped in a polystyrene sulfonate with a strong negative charge, and reacts with the magnesium-aluminum hydrotalcite nanosheet colloid to form a fluorescent sensing composite layer film. Between the multi-layer fluorescent sensing composite layer films, the polystyrene sulfonate containing disodium calcein is present between the magnesium-aluminum hydrotalcite layers. The fluorescent sensor prepared by constructing (covering) five layers of fluorescent sensing composite layer films on a quartz substrate can be used for the quantitative determination of the iron content in the reforming catalyst. The operation is simple, fast, and highly accurate. The hydrotalcite main layer of the fluorescent sensor is stable, non-toxic, and has good biocompatibility. Compared with other polymer carriers, it is not easy to age and has a long shelf life; the system to be tested is not polluted during the detection process and there is no reagent loss; the fluorescent signal of the used fluorescent sensor can be restored by EDTA (ethylenediaminetetraacetic acid), that is, the fluorescent sensor can be regenerated and reused.
[0018] In the fluorescence sensor described in the present invention, the quartz substrate is composed of a quartz plate and an assembly-aiding layer loaded on the quartz plate, and the assembly-aiding layer is diethylene glycol phthalate diacrylate. The ester can firmly bind polystyrene sulfonate groups thereon, thereby allowing the fluorescence sensing composite layer film to cover it.
[0019] The chemical composition of the magnesium aluminum hydrotalcite layer is [Mg 1-x Al x (OH)2](NO3) x , where 0.2≤x≤0.33, x is Al 3+ / (Mg 2+ +Al 3+ ).
[0020] The upper layer of each fluorescent sensing composite film of the five-layer fluorescent sensing composite film is a magnesium aluminum hydrotalcite layer, and the lower layer is a polystyrene sulfonate layer containing disodium calcein. The disodium calcein in the lower layer of the composite film is wrapped in polystyrene sulfonate.
[0021] The fluorescent sensor of the present invention is preferably used for the determination of iron content in naphtha catalytic reforming catalyst. The carrier of the reforming catalyst is alumina, and the loaded active metals are platinum and chlorine. In addition, a metal auxiliary agent may be contained, and the metal auxiliary agent is preferably tin or rhenium. In the catalyst, the platinum content based on the alumina carrier is 0.1-0.5% by mass, and the chlorine content is 0.5-2.0% by mass. Optionally, the tin content is 0.1-0.5% by mass, and the rhenium content is 0.2-0.6% by mass.
[0022] The method for preparing the fluorescent sensor of the present invention comprises:
[0023] (1) Under the protection of inert gas, formamide is added to the magnesium aluminum hydrotalcite precursor, and the mixture is stirred for sufficient reaction for 20 to 50 hours, and the upper clear liquid is taken as the magnesium aluminum hydrotalcite nanosheet colloid. The composition of the magnesium aluminum hydrotalcite precursor is [Mg 1-x Al x (OH)2](NO3) x ˙mH2O, where x is Al 3+ / (Mg 2+ +Al 3+ ), 0.2≤x≤0.33, m is the number of interlayer crystal water, and the maximum value of m is 0.81-x,
[0024] (2) preparing a mixed aqueous solution of calcein disodium salt and sodium polystyrene sulfonate, wherein the concentration of calcein disodium salt is 1×10 -3 mol / L,
[0025] (3) soaking the quartz plate in a mixed solution of concentrated H2SO4 and H2O2, and then soaking the obtained quartz plate in a diethylene glycol diacrylate (PDDA) solution for 10 to 40 minutes, taking it out and drying it to obtain a quartz substrate.
[0026] (4) soaking the quartz substrate prepared in step (3) in the mixed aqueous solution of calcein disodium salt and sodium polystyrene sulfonate prepared in step (2) for 5 to 25 minutes, washing with water, and then drying; and then soaking in the magnesium aluminum hydrotalcite nanosheet colloid prepared in step (1) for 5 to 25 minutes, washing with water, and drying, to obtain a fluorescent sensor having a fluorescent sensing composite layer film covered on the quartz substrate.
[0027] (5) Take the sensor prepared in step (4), repeat the steps of soaking, rinsing, and drying with the prepared mixed aqueous solution of calcein disodium salt and sodium polystyrene sulfonate in step (4), and then soaking, rinsing, and drying with magnesium aluminum hydrotalcite nanosheet colloid. The fluorescent sensor prepared each time is used for the preparation of the next fluorescent sensor, until five layers of fluorescent sensing composite layer film are covered on the quartz substrate.
[0028] The method (1) of the present invention is to prepare magnesium aluminum hydrotalcite nanosheet colloid, and the mass ratio of formamide to magnesium aluminum hydrotalcite precursor is 800 to 1300, preferably 900 to 1200. The inert gas is preferably nitrogen.
[0029] Step (2) is to prepare a mixed solution containing calcein disodium salt and sodium polystyrene sulfonate, wherein the content of sodium polystyrene sulfonate in the prepared mixed aqueous solution is 0.4-1.5 g / L, preferably 0.8-1.2 g / L.
[0030] The structural formula of the calcein disodium salt is:
[0031]
[0032] The structural formula of sodium polystyrene sulfonate is:
[0033]
[0034] The degree of polymerization n is preferably 240 to 500. The molecular weight of sodium polystyrene sulfonate is preferably 50,000 to 100,000, more preferably 60,000 to 80,000.
[0035] Step (3) is to prepare a quartz substrate. The quartz substrate is first soaked and cleaned with a mixed solution of concentrated H2SO4 and H2O2 solution, and then soaked with a diethylene glycol diacrylate phthalate (PDDA) solution to form a diethylene glycol diacrylate phthalate layer on the quartz substrate, which is convenient for growing a polystyrene sulfonate layer containing disodium calcein, and then growing a magnesium aluminum hydrotalcite layer, thereby forming a fluorescent sensing composite layer film. In the mixed solution of concentrated H2SO4 and H2O2 solution, the volume ratio of concentrated H2SO4 to H2O2 solution is preferably 2 to 3:1. The concentration of concentrated sulfuric acid is preferably 95 to 98% by mass, the concentration of H2O2 solution is 20 to 40% by mass, and the concentration of PDDA solution is preferably 0.5 to 2.0 g / L.
[0036] (3) After the quartz plate is soaked in the mixed solution of concentrated H2SO4 and H2O2 solution, it is preferably ultrasonically rinsed 1 to 5 times with water and ethanol alternately, each rinse time is 5 to 30 minutes, and then immersed in diethylene glycol phthalate diacrylate solution. The time for soaking the quartz plate in the mixed solution of concentrated H2SO4 and H2O2 solution is preferably 120 to 300 minutes.
[0037] The steps (4) and (5) are to cover the fluorescent sensing composite layer film on the quartz substrate, firstly, the diethylene glycol diacrylate layer on the quartz substrate is covered with a layer of polystyrene sulfonate containing disodium calcein, and then covered with a layer of magnesium aluminum hydrotalcite to form a layer of fluorescent sensing composite layer film, and then the layers are covered in the same way to form a total of five layers of fluorescent sensing composite layer film. The drying temperature described in the above method for preparing the composite layer film is preferably 20 to 40°C.
[0038] The hydrotalcite precursor is prepared by a hydrothermal synthesis method. Mg(NO3)2, Al(NO3)3, urea and water are made into a solution, so that the Mg / Al molar ratio is 1-3:1, the urea / Al molar ratio is 10-15:1, and the H2O / Al molar ratio is 3000-4500:1. The solution is reacted at 100-150°C under autogenous pressure for 12-48 hours, and after drying, a magnesium-aluminum hydrotalcite precursor with carbonate as anion is obtained.
[0039] A magnesium aluminum hydrotalcite precursor with carbonate as an anion is subjected to ion exchange by adding a small amount of 65-68 mass % concentrated HNO3 solution and 15-25 mass % NaNO3 solution, stirring for 24-72 hours under N2 protection at 0-30°C, and washing and drying the solid after ion exchange to obtain a magnesium aluminum hydrotalcite precursor with nitrate as anion. The drying temperature is preferably 50-80°C, more preferably 60-70°C.
[0040] The method for measuring the iron concentration in a solution using the fluorescent sensor provided by the present invention is as follows:
[0041] (1) preparing ferric chloride standard solutions of different concentrations, adding a small amount of H2O2 solution with a concentration of 20-40 mass %, sealing and protecting from light for later use;
[0042] (2) soaking the fluorescence sensor in a ferric chloride standard solution for 1 to 5 minutes, taking it out and drying it, measuring its fluorescence intensity with a fluorescence tester, and then drawing a standard curve based on the fluorescence intensity measured after the fluorescence sensor is soaked in each ferric chloride standard solution and the corresponding iron content in the ferric chloride standard solution;
[0043] (3) Take the iron-containing solution to be tested, add a small amount of H2O2 solution with a concentration of 20-30 mass %, immerse the fluorescence sensor in the solution to be tested for 1-5 minutes, take it out and dry it, measure its fluorescence intensity, and then determine the iron content according to the standard curve.
[0044] In the above method for determining the iron content in the solution, the fluorescence intensity is preferably the peak intensity (peak height) at a wavelength of 520 nm. The volume of the standard solution and the iron-containing solution to be measured can be 50-200 mL, and the amount of H2O2 solution added is 0.1-0.3 mL.
[0045] The method for determining the iron content in the catalyst is to first soak the catalyst to be tested in an acid solution to dissolve the iron in the catalyst in the acid solution, dilute it to a constant volume with water, and use the solution to be tested as the solution to be tested. The fluorescence sensor is placed in the solution to be tested and its fluorescence intensity value is determined according to the method in step (3) above. The iron content is then determined from the fluorescence intensity value using a standard curve.
[0046] The fluorescent sensor of the present invention can be regenerated after use. The regeneration method is to soak the used fluorescent sensor in a saturated EDTA solution for preferably 3 to 10 minutes, then take it out and dry it to obtain a fluorescent sensor with restored fluorescence intensity value. The regenerated fluorescent sensor can be reused.
[0047] The present invention is further described below by way of examples, but the present invention is not limited thereto.
[0048] Example 1
[0049] Preparation of magnesium aluminum hydrotalcite precursor
[0050] 0.008 mol of Mg(NO3)2˙6H2O, 0.004 mol of Al(NO3)3˙9H2O and 0.048 mol of urea were placed in a beaker, and 280 ml of deionized water was added and stirred to form a solution. The solution was transferred to a high-pressure melt bomb reactor with a polytetrafluoroethylene substrate and reacted at 110°C for 24 hours under closed conditions. The reaction product was washed with deionized water by centrifugation until the pH of the washing liquid was 7. The washed solid was dried at 60°C for 12 hours to obtain a magnesium aluminum hydrotalcite precursor with carbonate as anion, recorded as MgAl-CO3-LDH.
[0051] 0.3 g of MgAl-CO3-LDH and 63.73 g of NaNO3 were dissolved in 300 mL of deionized water (obtained by boiling deionized water with nitrogen) from which CO2 had been removed. After uniform dissolution, 0.08 mL of 65% by mass HNO3 solution was added, and the mixture was stirred at 25°C under N2 protection for 48 hours to carry out ion exchange. The mixture was then washed with deionized water from which CO2 had been removed at 25°C by centrifugation until the pH of the washing solution was 7. After washing, the solid was dried at 60°C for 12 hours to obtain a magnesium aluminum hydrotalcite precursor with nitrate as an anion, which was recorded as MgAl-NO3-LDH and had a chemical composition formula of [Mg6Al2(OH) 16 ](NO3)2·4H2O, where x=0.25, m=0.5.
[0052] Example 2
[0053] Preparation of the thin film fluorescence sensor of the present invention
[0054] (1) 0.1 g of the magnesium aluminum hydrotalcite MgAl-NO3-LDH prepared in Example 1 was added to 100 mL of formamide under nitrogen protection and stirred for 48 hours. The mixture was centrifuged and the supernatant was obtained as a colloidal solution of monolayer hydrotalcite nanosheets.
[0055] (2) 0.0666 g of calcein disodium salt, 0.12 g of sodium polystyrene sulfonate (molecular weight 70,000) and a certain amount of deionized water were prepared into a mixed solution. The pH value of the mixed solution was 7, and the concentration of calcein disodium salt was 1×10 - 3 mol / L, the concentration of sodium polystyrene sulfonate was 1.2 g / L, and it was stored in a 100 mL volumetric flask away from light.
[0056] (3) Take a quartz glass sheet (1.0 cm × 3.0 cm, thickness 0.1 cm), soak it in a mixed solution of concentrated H2SO4 (concentration 95 mass%) and H2O2 (concentration 30 mass%) in a volume ratio of 7:3 for 180 min, clean the surface of the quartz glass sheet, and then use deionized water and 99.7 mass % ethanol solution as rinsing liquids to perform ultrasonic rinsing three times alternately, with 40 ml of rinsing liquid used each time and the rinsing time being 20 min.
[0057] The rinsed quartz glass sheet was immersed in a 1.0 g / L diethylene glycol phthalate solution for 30 min, taken out and rinsed with 500 ml of deionized water, and dried with air at 25° C. to obtain a diethylene glycol phthalate layer supported on the quartz glass sheet, which was a quartz substrate.
[0058] (4) soaking the quartz substrate prepared in step (3) in the mixed solution containing disodium calcein prepared in step (2) for 20 minutes, taking it out and washing it with deionized water, and drying it with air at 25° C.; then soaking it in the colloidal solution of the single-layer hydrotalcite nanosheet prepared in step (1) for 20 minutes, taking it out and washing it with deionized water, and drying it with air at 25° C. to obtain a fluorescent sensor having a fluorescent sensing composite layer film covered on the quartz substrate, wherein the upper layer of the composite layer film is a magnesium-aluminum hydrotalcite layer, and the lower layer is a polystyrene sulfonate layer containing calcein, and the chemical composition of the layer of the magnesium-aluminum hydrotalcite layer is [Mg6Al2(OH) 16 ](NO3)2.
[0059] (5) Take the fluorescent sensor prepared in step (4), and repeat the operation of step (4) 4 times. Each time the operation is repeated, a layer of fluorescent sensing composite layer film is added on the quartz substrate. The fluorescent sensor prepared each time is used to prepare the next fluorescent sensor, until 5 layers of fluorescent sensing composite layer films are covered on the quartz substrate. A fluorescent sensor with 5 layers of fluorescent sensing composite layer films covered on the quartz substrate is obtained, which is recorded as fluorescent sensor A. Its fluorescence intensity value is shown in Figure 3 , UV-visible absorption spectrum is shown in Figure 4 ,Depend on Figure 4 It can be seen that with the increase in the number of composite film layers, the peak height of the ultraviolet absorption peak at 502nm also increases, but the peak height of the ultraviolet absorption peak at 502nm of the fifth composite film increases little compared to the fourth composite film, and has basically reached saturation.
[0060] The fluorescence intensity values of the fluorescent sensor composite layer films with different numbers of layers obtained during the preparation process of the fluorescent sensor A are shown in Figure 5 , Figure 5 It shows that as the number of fluorescent sensing composite layers increases, the fluorescence intensity value increases, indicating that the content of calcein disodium salt in the fluorescent sensor also increases with the increase in the number of composite layers.
[0061] Example 3
[0062] The fluorescence sensor was prepared according to the method of Example 2, except that the concentration of sodium polystyrene sulfonate in the polystyrene sulfonate solution containing disodium calcein prepared in step (2) was 0.4 g / L. The fluorescence sensing composite layer film was prepared by repeating the operation 5 times to obtain a fluorescence sensor B having 5 layers of fluorescence sensing composite layer films on a quartz substrate. The fluorescence signal value is shown in FIG. Figure 3 .
[0063] Example 4
[0064] The fluorescence sensor was prepared according to the method of Example 2, except that the concentration of sodium polystyrene sulfonate in the sodium polystyrene sulfonate solution containing disodium calcein prepared in step (2) was 0.8 g / L. The fluorescence sensing composite layer film was prepared by repeating the operation 5 times to obtain a fluorescence sensor C having 5 layers of fluorescent sensing composite layer films on a quartz substrate. The fluorescence intensity value is shown in FIG. Figure 3 .
[0065] Example 5
[0066] The fluorescence sensor was prepared according to the method of Example 2, except that the concentration of sodium polystyrene sulfonate in the polystyrene sulfonate solution containing disodium calcein prepared in step (2) was 1.0 g / L. The fluorescence sensing composite layer film was prepared by repeating the operation 5 times to obtain a fluorescence sensor D having 5 layers of fluorescence sensing composite layer films on a quartz substrate. The fluorescence intensity value is shown in FIG. Figure 3 .
[0067] Example 6
[0068] The fluorescence sensor was prepared according to the method of Example 2, except that the concentration of sodium polystyrene sulfonate in the polystyrene sulfonate solution containing disodium calcein prepared in step (2) was 1.5 g / L. The fluorescence sensing composite layer film was prepared by repeating the operation 5 times to obtain a fluorescence sensor E having 5 layers of fluorescence sensing composite layer films on a quartz substrate. The fluorescence intensity value is shown in FIG. Figure 3 .
[0069] Comparative Example 1
[0070] The fluorescence sensor was prepared according to the method of Example 2, except that the solution of calcein disodium salt was prepared in step (2) without sodium polystyrene sulfonate. The operation was repeated 5 times to prepare a fluorescence sensor composite layer film, and a fluorescence sensor M having 5 layers of fluorescence sensor composite layer films covered on a quartz substrate was obtained. The fluorescence intensity value is shown in FIG. Figure 3 .
[0071] Example 7
[0072] Test the fluorescence response value of the fluorescence sensor to different concentrations of FeCl3 solution
[0073] 100 mL of FeCl3 solution with iron content of 10 ppm, 50 ppm, 100 ppm, 500 ppm and 1000 ppm were prepared respectively, and 0.1 mL of H2O2 solution with a concentration of 30 mass % was added thereto to obtain test solution. Five fluorescent sensors A were prepared according to the method of Example 2, and the five fluorescent sensors were placed in cuvettes respectively, and added to the FeCl3 test solution with different iron content prepared above respectively, and soaked for 3 minutes. After taking out and drying, the fluorescence intensity values were measured respectively. The results are shown in FIG. Figure 6 .Depend on Figure 6 It can be seen that the fluorescence intensity of the fluorescence sensor at 520nm gradually decreases with the increase of the iron content in the test solution. The iron content-fluorescence intensity value standard curve is drawn by the fluorescence intensity values of the test solutions with different iron contents at 520nm, which is used to determine the iron content of unknown samples.
[0074] Example 8
[0075] This example determines the iron content in the reforming catalyst
[0076] 0.22 g of reforming catalyst used in industrial equipment was added with hydrochloric acid and dissolved by closed pressurized wet chemical digestion, diluted to 100 mL with deionized water, and then 0.1 mL of 30% by mass H2O2 solution was added to obtain an iron-containing reforming catalyst test solution. The reforming catalyst includes a γ-alumina carrier and 0.28% by mass of platinum, 0.31% by mass of tin and 1.22% by mass of chlorine based on the carrier.
[0077] The fluorescent sensor A prepared in Example 2 was placed in a cuvette, added to the reforming catalyst test solution and soaked for 3 minutes, taken out and blown dry, and the fluorescence intensity of the fluorescent sensor at 520nm was measured. The iron content in the catalyst was measured to be 22.4ppm based on the standard curve drawn in Example 7, and the iron content of the catalyst tested by inductively coupled plasma atomic emission spectrometry (ICP / AES) was 22.1ppm. This shows that the fluorescent sensor prepared by the present invention can quickly measure the iron content in the catalyst, and the measurement accuracy is equivalent to the value measured by the standard method.
[0078] Example 9
[0079] Investigation of the regeneration and reuse performance of the fluorescent sensor of the present invention
[0080] The fluorescent sensor after the catalyst solution used in Example 8 was taken, denoted as A-Fe, and soaked in a solution with an EDTA concentration of 0.3 mass% for 5 minutes. After being taken out and dried, the regenerated fluorescent sensor was obtained, denoted as A-Fe-EDTA, and its fluorescence intensity was measured again. The results are shown in FIG. Figure 7 .
[0081] Depend on Figure 7 It can be seen that the fluorescence intensity of the used fluorescent sensor at 520 nm decreases, and after being immersed in the EDTA solution, the fluorescence intensity at 520 nm increases again, which is close to the fluorescence intensity of the unused fluorescent sensor A, indicating that the fluorescent sensor of the present invention can be regenerated and reused.
Claims
1. A thin film fluorescence sensor for measuring the iron content in a reforming catalyst, comprising a quartz substrate and five layers of fluorescence sensing composite layer films covered thereon, wherein the quartz substrate comprises a quartz sheet and an assembly-aiding layer supported on the quartz sheet, wherein the assembly-aiding layer is a diethylene glycol diacrylate phthalate layer, wherein the upper layer of each layer of the fluorescence sensing composite layer film is a magnesium aluminum hydrotalcite layer, and the lower layer is a polystyrene sulfonate layer containing disodium calcein, wherein the carrier in the reforming catalyst is alumina, and the supported active metals are platinum and chlorine.
2. The fluorescence sensor according to claim 1, characterized in that The chemical composition of the magnesium aluminum hydrotalcite layer is [Mg 1-x Al x (OH)2](NO3) x , where x is Al 3+ / (Mg 2+ +Al 3+ ), 0.2≤x≤0.
33.
3. The fluorescence sensor according to claim 1, characterized in that The calcein disodium salt in the lower layer of the composite film is wrapped in polystyrene sulfonate.
4. The fluorescence sensor according to claim 1, characterized in that The catalyst is a naphtha catalytic reforming catalyst.
5. A method for preparing the fluorescent sensor according to claim 1, comprising: (1) Under the protection of inert gas, formamide is added to the magnesium aluminum hydrotalcite precursor, and the mixture is stirred for sufficient reaction for 20 to 50 hours, and the upper clear liquid is taken as the magnesium aluminum hydrotalcite nanosheet colloid. The composition of the magnesium aluminum hydrotalcite precursor is [Mg 1-x Al x (OH)2](NO3) x ˙mH2O, where x is Al 3+ / (Mg 2+ +Al 3+ ), 0.2≤x≤0.33, m is the number of interlayer crystal water, and the maximum value of m is 0.81-x, (2) preparing a mixed aqueous solution of calcein disodium salt and sodium polystyrene sulfonate, wherein the concentration of calcein disodium salt is 1×10 -3 mol / L, (3) soaking the quartz plate in a mixed solution of concentrated H2SO4 and H2O2, and then soaking the obtained quartz plate in a diethylene glycol diacrylate (PDDA) solution for 10 to 40 minutes, taking it out and drying it to obtain a quartz substrate. (4) soaking the quartz substrate prepared in step (3) in the mixed aqueous solution of calcein disodium salt and sodium polystyrene sulfonate prepared in step (2) for 5 to 25 minutes, washing with water, and then drying; and then soaking in the magnesium aluminum hydrotalcite nanosheet colloid prepared in step (1) for 5 to 25 minutes, washing with water, and drying, to obtain a fluorescent sensor having a fluorescent sensing composite layer film covered on the quartz substrate. (5) Take the sensor prepared in step (4), repeat the steps of soaking, rinsing, and drying with the prepared mixed aqueous solution of calcein disodium salt and sodium polystyrene sulfonate in step (4), and then soaking, rinsing, and drying with magnesium aluminum hydrotalcite nanosheet colloid. The fluorescent sensor prepared each time is used for the preparation of the next fluorescent sensor, until five layers of fluorescent sensing composite layer film are covered on the quartz substrate.
6. The method according to claim 5, characterized in that The mass ratio of formamide to magnesium aluminum hydrotalcite precursor used in step (1) is 800-1300.
7. The method according to claim 5, characterized in that The content of sodium polystyrene sulfonate in the mixed aqueous solution of calcein disodium salt and sodium polystyrene sulfonate prepared in step (2) is 0.4-1.5 g / L.
8. The method according to claim 5, characterized in that In the mixed solution of concentrated H2SO4 and H2O2 in step (3), the volume ratio of concentrated H2SO4 to H2O2 solution is 2 to 3:
1.
9. The method according to claim 5, characterized in that (3) After the quartz plate is soaked in a mixed solution of concentrated H2SO4 and H2O2, it is then ultrasonically rinsed with water and ethanol alternately for 1 to 5 times, each rinse time being 5 to 30 minutes, and then immersed in a diethylene glycol diacrylate phthalate solution.
10. The method according to claim 5, characterized in that The drying temperature in step (4) is 10-30°C.
Citation Information
Patent Citations
Fluorescent sensor for magnesium ions and preparation method thereof
CN102053079A
Melamine concentration fluorescent sensor and production method thereof
CN105866087A